2008
DOI: 10.2337/dc07-2065
|View full text |Cite
|
Sign up to set email alerts
|

Soy Protein Intake, Cardiorenal Indices, and C-Reactive Protein in Type 2 Diabetes With Nephropathy

Abstract: OBJECTIVE -Several short-term trials on the effect of soy consumption on cardiovascular risks are available, but little evidence exists regarding the impact of long-term soy protein consumption among type 2 diabetic patients with nephropathy. To determine the effects of long-term soy consumption on cardiovascular risks, we measured C-reactive protein (CRP) and kidney function indexes among type 2 diabetic patients with nephropathy. RESEARCH DESIGN AND METHODS -This longitudinal randomized clinical trial was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
178
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(194 citation statements)
references
References 24 publications
9
178
0
7
Order By: Relevance
“…Many experimental and clinical data suggest that inflammatory cell infiltration, cytokines and inflammatory mediators increase in DN [12][13]. A key role might be played by inflammation in the diabetic renal pathogenesis injury alone [14][15][16]. The results of this experiment also confirmed that the levels of ED-1, CRP and TNF-α in renal tissue increased in DN rats, indicating that there was a significant inflammatory reaction process in diabetic nephropathy.…”
Section: The Effect Of Tgf-β1 Mrna Expression In Kidney Tissuessupporting
confidence: 65%
“…Many experimental and clinical data suggest that inflammatory cell infiltration, cytokines and inflammatory mediators increase in DN [12][13]. A key role might be played by inflammation in the diabetic renal pathogenesis injury alone [14][15][16]. The results of this experiment also confirmed that the levels of ED-1, CRP and TNF-α in renal tissue increased in DN rats, indicating that there was a significant inflammatory reaction process in diabetic nephropathy.…”
Section: The Effect Of Tgf-β1 Mrna Expression In Kidney Tissuessupporting
confidence: 65%
“…Interesting results have been reported by studies of soy consumption. Thus, TNF-a levels were significantly lower in the soy nut group compared with the soy protein and control groups as this was demonstrated by Azadbakht et al (2008) implying a role in the soya lipid fraction. In contrast to these findings, Jenkins et al (2002) showed that there was no significant effect on interleukin-6 or TNF-a in middle-aged men and women on the highisoflavone versus the low-isoflavone soy food diet.…”
Section: Effect Of Oil Acute Consumption On Adhesion Moleculesmentioning
confidence: 63%
“…The efficacy of soy protein intake on lowering the risk of coronary heart disease has been accepted by the US Food and Drug Administration [10]. Consumption of soy protein significantly lowers cardiovascular risks by affecting fasting plasma glucose, TC, LDL-C, serum TG, and C-reactive protein [11], and soy protein supplementation is thought to be an effective management strategy for metabolic and vascular diseases [12]. However, much less is known regarding the health benefits of rice protein.…”
Section: Introductionmentioning
confidence: 99%